HOW ENGLISH STUDENT TEACHERS DEAL WITH TEACHING DIFFICULTIES IN THEIR TEACHING PRACTICUM - Riesky, Riesky (Universitas Pendidikan Indonesia, 2013)
Abstract: In the process of becoming professional, every single teacher will normallygo through a series of experiences that are cognitively, physically, and emotionallychallenging. One of the first steps they have to go through is a form of first teachingexperience with real students and real school environment like what many studentteachers are required to face in their teaching practicum. This paper explores kindsof teaching difficulties and efforts carried out to overcome them by English studentteachers in the context of teaching practicum conducted in 14 different secondaryschools in Bandung, Indonesia. Qualitative case study is applied as the research design,with interviews as the main instrument in collecting the data. This study involves theparticipation of students enrolled in an EFL Methodology class in collecting the dataas a part of their course assignment. The results of data analysis reveal that there are avariety of problems that can be mainly categorised into three types, namely problemsrelated to students, to the supervising teachers, and to the student teachers themselves.Several efforts carried out are also identified and some suggestions are also highlightedat the end of the paper.